Global equivalent magnetization of the oceanic lithosphere - Dyment, J.; Choi, Y.; Hamoudi, M.; Lesur, V.; Thébault, Erwan (Earth and Planetary Science Letters, 2015)
International audience As a by-product of the construction of a new World Digital Magnetic Anomaly Map over oceanic areas, we use an original approach based on the global forward modeling of seafloor spreading magnetic anomalies and their comparison to the available marine magnetic data to derive the first map of the equivalent magnetization over the World's ocean. This map reveals consistent patterns related to the age of the oceanic lithosphere, the spreading rate at which it was formed, and the presence of mantle thermal anomalies which affects seafloor spreading and the resulting lithosphere. As for the age, the equivalent magnetization decreases significantly during the first 10-15 Myr after its formation, probably due to the alteration of crustal magnetic minerals under pervasive hydrothermal alteration, then increases regularly between 20 and 70 Ma, reflecting variations in the field strength or source effects such as the acquisition of a secondary magnetization. As for the spreading rate, the equivalent magnetization is twice as strong in areas formed at fast rate than in those formed at slow rate, with a threshold at ∼40 km/Myr, in agreement with an independent global analysis of the amplitude of Anomaly 25. This result, combined with those from the study of the anomalous skewness of marine magnetic anomalies, allows building a unified model for the magnetic structure of normal oceanic lithosphere as a function of spreading rate. Finally, specific areas affected by thermal mantle anomalies at the time of their formation exhibit peculiar equivalent magnetization signatures, such as the cold Australian-Antarctic Discordance, marked by a lower magnetization, and several hotspots, marked by a high magnetization.